Territorial Behavior and Social Stability in the Mouse Require Correct Expression of Imprinted Cdkn1c - McNamara, Gráinne I.; John, Rosalind M.; Isles, Anthony R. (Frontiers in Behavioral Neuroscience, 2018)
Genomic imprinting, the epigenetic process by which transcription occurs from a single parental allele, is believed influence social behaviours in mammals. An important social behaviour is group living, which is enriched in Eutherian mammals relative to monotremes and marsupials. Group living facilitates resource acquisition, defence of territory and co-care of young, but requires a stable social group with complex inter-individual relationships. Co-occurring with increased group living in Eutherians is an increase in the number of imprinted loci, including that spanning the maternally expressed Cdkn1c. Using a ‘loss-of-imprinting’ model of Cdkn1c (Cdkn1cBACx1), we demonstrated that two-fold over expression of Cdkn1c results in abnormal social behaviours. Although our previous work indicated that male Cdkn1cBACx1 mice were more dominant as measured by tube-test encounters with unfamiliar wild-type males. Building upon this work, using more ecologically relevant assessments of social dominance, indicated that within their normal social group, Cdkn1cBACx1 mice did not occupy higher ranking positions. Nevertheless, we find that presence of Cdkn1cBACx1 animals within a group leads to instability of the normal social hierarchy, as indicated by greater variability in social rank within the group over time and an increase in territorial behaviour in WT cage-mates. Consequently, these abnormal behaviours led to an increased incidence of fighting and wounding within the group. Taken together these data indicate that normal expression of Cdkn1c is required for maintaining stability of the social group and suggests that the acquisition of monoallelic expression of Cdkn1c may have enhanced social behaviour in Eutherian mammals to facilitate group living.